Prototipe Alat Monitoring Suhu dan Kelembapan Ruang Baterai pada Gardu Induk Berbasis IoT - Meunasah, Adinda Rahma Satya; Rahmadani, Arief (Majalah Ilmiah Teknologi Elektro; Vol 23 No 2 (2024): (Juli - Desember) Majalah Ilmiah Teknologi Elektro, 2024)
The battery room is always maintained at a certain temperature and humidity level to prevent the batteries from degrading due to high temperatures and poor air circulation. The aim of this study is to develop a system for monitoring and controlling the temperature and humidity in the battery room, ensuring the reliability of the power supply. The method used includes designing the mechanical and electrical prototype system and developing the controller program, followed by testing the entire system. The system consists of an STM32F103C8T6 microcontroller using a DHT-22 sensor to measure the temperature and humidity in the battery room, a voltage sensor to measure the battery voltage, and an exhaust fan. The test results showed a temperature measurement error of 0.2%, a humidity error of 4.04%, and an average battery voltage error of 0.5%. The exhaust fan operates with a duty cycle control that generates input voltages of 29.8 V, 34.88 V, and 42.88 V, which align with the standard temperature and humidity values in the battery room.